Relatives' negotiation power in relation to older people's acute hospital admission: A qualitative interview study. Issue 4 (22nd June 2021) - Hoffmann, Eva; Andersen, Pernille Tanggaard; Mogensen, Christian Backer; Prinds, Christina; Primdahl, Jette
Abstract: Background: Acutely admitted older people are potentially vulnerable and dependent on relatives to negotiate and navigate on their behalf. Aim: This study aimed to explore relatives' experiences of their interactions with healthcare professionals during acute hospital admission of older people to derive themes of importance for relatives' negotiations with these professionals. Method: A qualitative design was applied. Relatives of acutely admitted older people at two emergency departments in Denmark were interviewed ( n = 17). The qualitative content analysis was guided by Graneheim and Lundman's concepts. Results: The analysis derived four themes: (a) Mandate, (b) Incentive, (c) Capability and (d) Attitude to taking action . These four sources of relatives' negotiation power can be illustrated in the MICA model. Conclusion: Four themes were identified as important sources of relatives' negotiation power. Since the four sources of power potentially change according to the situation, relatives' negotiation power seems to be context dependent.